Nutritional status and risk factors for malnutrition among children aged 1–6 years in tribal communities of Malappuram district, Kerala: a cross-sectional study - Anjaly Perayil; Sreelakshmi Mohandas K (BMJ Public Health)
Introduction Malnutrition has critical consequences for physical and cognitive growth, as well as for development. In Kerala, Malappuram district has the highest burden of malnutrition and is home to nearly half of the Paniya tribal population of the state.Objective To estimate the prevalence of undernutrition and the factors associated with the nutritional status of tribal children 1–6 years of age in Malappuram district of Kerala, India.Methods A community-based cross-sectional study was carried out between April to September 2022 among the tribal settlements in Nilamboor, Perinthalmanna and Edavanna, divisions of Malappuram district. A multistage cluster sampling was done and the minimum calculated sample size was 142. Parents of each child were interviewed using a semi-structured questionnaire along with anthropometric measurements for estimating height and weight. Data were analysed using ENA software and SPSS V.20.Results The prevalence of underweight, stunting and wasting were found to be 43%, 41.4% and 34.7%, respectively. Among them, 14%, 21.3% and 8.5% were severely underweight, severely stunted and severely wasted in this study population. Socio-demographic characteristics like maternal and paternal unemployment, maternal illiteracy, maternal habits like alcohol consumption, chewing tobacco and acute morbidities among children like diarrhoea and cough were found to be independent predictors for underweight among the tribal children of Malappuram district. Maternal unemployment and alcohol consumption were found to be independent predictors for stunting. For wasting, paternal unemployment, weaning practices and episodes of diarrhoea were found to be independent predictors.Conclusion Socio-demographic factors like parental unemployment, illiteracy and habits like alcohol consumption and tobacco use strongly influence the nutritional status of tribal children. An appropriately planned educational campaign and targeted interventions for improving nutritional status have to be deployed in these tribal communities.